Nuclear receptor NR2F6 inhibition potentiates responses to PD-L1/PD-1 cancer immune checkpoint blockade - Klepsch, Victoria; Hermann-Kleiter, Natascha; Do-Dinh, Patricia; Jakic, Bojana; Offermann, Anne; Efremova, Mirjana; Sopper, Sieghart; Rieder, Dietmar; Krogsdam, Anne; Gamerith, Gabriele; Perner, Sven; Tzankov, Alexandar; et al. (Nature communications, 2018)
Analyzing mouse tumor models in vivo, human T cells ex vivo, and human lung cancer samples, we provide direct evidence that NR2F6 acts as an immune checkpoint. Genetic ablation of Nr2f6 , particularly in combination with established cancer immune checkpoint blockade, efficiently delays tumor progression and improves survival in experimental mouse models. The target genes deregulated in intratumoral T lymphocytes upon genetic ablation of Nr2f6 alone or together with PD-L1 blockade reveal multiple advantageous transcriptional alterations. Acute Nr2f6 silencing in both mouse and human T cells induces hyper-responsiveness that establishes a non-redundant T-cell-inhibitory function of NR2F6. NR2F6 protein expression in T-cell-infiltrating human NSCLC is upregulated in 54% of the cases ( n = 303) and significantly correlates with PD-1 and CTLA-4 expression. Our data define NR2F6 as an intracellular immune checkpoint that suppresses adaptive anti-cancer immune responses and set the stage for clinical validation of targeting NR2F6 for next-generation immuno-oncological regimens. Immune checkpoints blockade (ICB) is a viable anti-cancer strategy. Here the authors show that nuclear receptor NR2F6 acts as an immune checkpoint in T cells and, using mouse models and human T cells, they show NR2F6 inhibition might improve current ICB therapy or work as an alternative therapeutic strategy.